Analysis of extracellular RNA in cerebrospinal fluid. Issue 1 (1st December 2017) - Saugstad, Julie A.; Lusardi, Theresa A.; Van Keuren-Jensen, Kendall R.; Phillips, Jay I.; Lind, Babett; Harrington, Christina A.; McFarland, Trevor J.; Courtright, Amanda L.; Reiman, Rebecca A.; Yeri, Ashish S.; Kalani, M. Yashar S.; Adelson, P. David; et al.
ABSTRACT: We examined the extracellular vesicle (EV) and RNA composition of pooled normal cerebrospinal fluid (CSF) samples and CSF from five major neurological disorders: Alzheimer's disease (AD), Parkinson's disease (PD), low-grade glioma (LGG), glioblastoma multiforme (GBM), and subarachnoid haemorrhage (SAH), representing neurodegenerative disease, cancer, and severe acute brain injury. We evaluated: (I) size and quantity of EVs by nanoparticle tracking analysis (NTA) and vesicle flow cytometry (VFC), (II) RNA yield and purity using four RNA isolation kits, (III) replication of RNA yields within and between laboratories, and (IV) composition of total and EV RNAs by reverse transcription–quantitative polymerase chain reaction (RT-qPCR) and RNA sequencing (RNASeq). The CSF contained 106 EVs/μL by NTA and VFC. Brain tumour and SAH CSF contained more EVs and RNA relative to normal, AD, and PD. RT-qPCR and RNASeq identified disease-related populations of microRNAs and messenger RNAs (mRNAs) relative to normal CSF, in both total and EV fractions. This work presents relevant measures selected to inform the design of subsequent replicative CSF studies. The range of neurological diseases highlights variations in total and EV RNA content due to disease or collection site, revealing critical considerations guiding the selection of appropriate approaches and controls for CSF studies.